The Murder of a Pawnbroker and the Gentlemen's Duel. - Sánchez, Roberto (Studies in Latin American Popular Culture, 2024)
This article takes a microhistorical look at the underside of Afro-Peruvian culture to analyze the cultural and political intersection of plebeian and elite spheres. It examines two sensational crimes involving Afro-Peruvians that captured the zeitgeist of early twentieth-century Lima. The first involves the murder of the wealthiest pawnbroker in Lima at the hands of Apolinario Arzola, an infamous Afro-Peruvian criminal demonized and used by the press and social commentators to reinforce notions of good and evil framed in terms of race. The second crime was a sensationalized duel between two Afro-Peruvians from the traditionally Black neighborhood of Malambo. It captured the popular imagination, as evidenced in newspaper reports and interviews, court records, prison correspondence, songs, and the memories of limeños more than one hundred years after the event. The Peruvian modernization project of the period examined signaled a change in urban codes of honor and deepened the marginalization of the underclass and Afro-Peruvians. The incorporation of their cultural expressions in the areas of the arts, sports, political movements, and other forms of urban popular culture changed the meaning of how creole culture was defined and woven into a formation of a conflicted national identity.